Brain imaging biomarkers in Multiple Sclerosis - Altokhis, Amjad (2023)
Background: Iron rim lesions (IRLs), white matter lesions (WMLs) accumulation and linear brain atrophy measurements have been suggested to be important imaging biomarkers in multiple sclerosis (MS). The extent to which these markers are related to MS diagnosis and predict disease prognosis remains unclear. Furthermore, research Magnetic Resonance Imaging (MRI) findings need validation in clinical settings before they can be incorporated into clinical practice.